A guided tour in haptic audio visual environments and applications. (4th June 2007) - Eid, Mohamad; Orozco, Mauricio; El Saddik, Abdulmotaleb
The science of haptics has received enormous attention in the last decade. Activities in different disciplines such as robotics, computer graphics, and psychophysics have been the foundation of haptic science. Nowadays, haptic research comprises four interdisciplinary research branches: human haptics, machine haptics, computer haptics, and the newly introduced multimedia haptics. This paper traces the evolution of haptics technology from the introductory concepts and haptic system architecture, to current technology in the four haptics research branches and applications. Finally, we summarise our findings and present a vision for overcoming challenges and our direction for future research in this area.